An effective one-pot access to polynuclear dispiroheterocyclic structures comprising pyrrolidinyloxindole and imidazothiazolotriazine moieties via a 1,3-dipolar cycloaddition strategy - Izmest’ev, Alexei N.; Gazieva, Galina A.; Sigay, Natalya V.; Serkov, Sergei A.; Karnoukhova, Valentina A.; Kachala, Vadim V.; Shashkov, Alexander S.; Zanin, Igor E.; Kravchenko, Angelina N.; Makhova, Nina N. (Beilstein Journal of Organic Chemistry, 2016)
An effective and highly regio- and diastereoselective one-pot method for the synthesis of new polynuclear dispiroheterocyclic systems with five stereogenic centers (dispiro[imidazo[4,5-e]thiazolo[3,2-b]-1,2,4-triazine-6,3′-pyrrolidine-2′,3′′-indoles]) comprising pyrrolidinyloxindole and imidazo[4,5-e]thiazolo[3,2-b]-1,2,4-triazine moieties has been developed. The method relies on a 1,3-dipolar cycloaddition of azomethine ylides generated in situ from isatin derivatives and sarcosine to 6-benzylideneimidazo[4,5-e]thiazolo[3,2-b]-1,2,4-triazine-2,7-diones.
Keywords: azomethine ylides; cycloaddition; diastereoselectivity; nitrogen heterocycles; spiro compounds